FCSIT ALUMNI INFORMATION SYSTEM - AFIQ IMRAN, ROSLAN (Universiti Malaysia Sarawak, (UNIMAS), 2023)
Alumni plays a variety of important roles, including assisting an institution's development and growth. Alumni can also help universities with mentoring, internships, and job opportunities. The university will have to spend more time tracing alumni detailsif there is no proper way to find out about them. Thus, collecting accurate data will be a significant benefit for the university. Faculty of Computer Science and Information Technology, Universiti Malaysia Sarawak has a problem to identify their alumni because of the faculty does not has a system that store their alumni details. Thus, this situation is making the Deputy Dean of Student Welfare and Alumni hard to contact the alumni. The Web-Based application is a great technology that the university can utilise to develop an Alumni Information System. This system can assist the faculty in keeping track of alumni information, spreading news, and much more. This project will create an Alumni Information System for Universiti Malaysia Sarawak's Faculty of Computer Science and Information Technolog